The Effect of Ownership Structure, Audit Committee, Company Size, and Audit Quality on the Integrity of Financial Statements on Manufacturing Companies Listed on IDX - Hanny Oktaviana; Melvie Paramitha (Newinera Publisher, 2021)
A list of financial data (e.g., account balances, transactions, and changes in value) is given over a period of time. This information may be utilized by readers of financial statements to help them make economic choices. So, the businesses that want to be trusted must provide honest financial accounts. The study sought to investigate the relationships between several measures of corporate control, management control, the audit committee, and size, on the accuracy of financial statements for manufacturer companies listed on the IDX. The population utilized in this study consists of 169 businesses, while the sample is made up of just 43 companies. This study used the assistance of SmartPLS software to analyze the information. The study's findings indicate that Institutional Ownership and the Audit Committee are linked to financial statements' integrity. Meanwhile, these three factors (i.e., size of the company, level of managerial ownership, and audit quality) have no impact on the financial statements' integrity.